I’m Not Good for Anything and That’s Why I’m Stressed: Analysis of the Effect of Self-Efficacy and Emotional Intelligence on Student Stress Using SEM and QCA - Navarro-Mateu, Diego; Alonso-Larza, Lucía; Gómez-Domínguez, María Teresa; Prado-Gascó, Vicente; Valero-Moreno, Selene (Frontiers in Psychology, 2020)
Stress negatively affects the well-being and quality of life of society. Specifically in the academic context, it is relevant to analyse its levels due to its impact on performance and learning. There are factors which affect said stress including, among others, self-efficacy and emotional intelligence. The purpose of this study is to analyse how emotional intelligence and perceived self-efficacy affect student stress. In order to show this influence, two complementary methodologies are implemented: the structural equation models (SEM) and the comparative qualitative analysis (QCA). A total of 477 students (85% of women) from a private University of Valencia participated in the study, with ages ranging from 18-53 years old (M=21.57, SD=3.68). The assessment instruments used were as follows: Emotional Intelligence Scale (TMMS-24) to measure emotional intelligence; General Self-Efficacy Scale (GSS) to measure self-efficacy; and Perceived Stress Scale (PSS) to measure stress. The results in SEM endorse the hypotheses that emotional clarity and self-efficacy are negatively related to stress and positively related to emotional attention, explaining 25% of the variance. The QCA results show that none of the variables is a necessary condition for inducing stress. Nevertheless, different combinations of these variables are sufficient conditions to explain 35% of the high stress levels. The most important combination over high stress levels seems to be the interaction between high levels of emotional attention and low levels of self-efficacy. Regarding to the low levels of perceived stress, there are sufficient conditions to explain 50% of them. Mainly, the most important interaction is between low levels of self-efficacy and low levels of emotional attention. The comparison of both methodologies enables the broadening of new horizons at the methodological level applicable to different contexts.